Microwave-assisted pyrolysis of furfural residue in a continuously operated auger reactor: Biochar characterization and analysis. (1st February 2019) - Mao, Xiao; Kang, Qinhao; Liu, Yang; Siyal, Asif Ali; Ao, Wenya; Ran, Chunmei; Fu, Jie; Deng, Zeyu; Song, Yongmeng; Dai, Jianjun
Abstract: Microwave-assisted pyrolysis (MWAP) of furfural residue (FR) was performed in a continuously operated auger reactor. The effects of temperature and additives on pyrolysis products and char properties were investigated. The yield of FRBC (furfural residue biochar) decreased to 43.62 wt.% and non-condensable gas yield increased to 40.37 wt.% with temperature increasing to 750 °C. However, condensate yield increased with increasing temperature from 450 to 550 °C, reaching maximum (i.e. 21.49 wt.%) at 550 °C, then decreased to 15.65 wt.% as temperature reached 750 °C. Kaolin and K2 CO3 promoted production of non-condensable gases and CaO increased the yield of FRBC. The relative proportion (RP) values of carbon, hydrogen, nitrogen and sulfur in FRBC were 50.49–65.07 wt.%, 13.05–26.81 wt.%, 61.99–79.84 wt.% and 60.93–74.16 wt.%, respectively. The highest iodine adsorption value of 127mg/g and methylene blue number of 59 mg/g were achieved for FRBC at 450 °C. Kaolin, CaO and K2 CO3 increased methylene blue number, and K2 CO3 significantly increased iodine adsorption capacity of FRBC. CaO retained sulfur, chlorine, zinc, and kaolin showed greater retention capacities for copper, nickel, chromium and zinc. The major crystalline phases of sulfur and nitrogen were CaSO4, K2 Ca2 (SO4 )3, Zr(NO3 )4 in FRBC and K2 Ca2 (SO4 )3 in FR. Highlights: Kaolin and K2 CO3 increased non-condensable gas yield, CaO increased biochar yield. Highest iodine adsorption value of 127mg/g was achieved for biochar at 450°C. Highest methylene blue number of 59mg/g was achieved for biochar at 450°C. CaO retained S, Cl and Zn, kaolin showed retention capacities for Cu, Ni, Cr, Zn. Sulfur and nitrogen mainly existed as CaSO4, K2 Ca2 (SO4 )3 and Zr(NO3 )4 in biochar.